Filosofia trascendentale e teorie dell’immagine - Furlani, Simone (Scenari, 2021)
This paper discusses the relation between transcendental philosophy and visual studies, which only apparently is an irreducible one. A ‘genealogical’ analysis of the current notions of image finds in Kant’s doctrine of image and in the later idea of reality as “fluid” reality (Maimon and Nietzsche) some theoretical structures that offer the visual studies an unknown point of view: the image as ‘reification’. This negative meaning of image exceeds the idea of an ‘iconic’ or ‘pictorial turn’ and supports a particular kind of sight, that overrides the images and gives priority to the sign, not only inside the images, but also in the reality. Roland Barthes calls this sight “punctum”, the only way to avoid the reifying power of the images and to be able to see and ‘read’ the reality.